The (dis)continuing of antithrombotic drugs and its implications for occurrence of adverse cardiovascular and bleeding events in cancer patients during end of life - Aldridge, Sarah J; Akbari, Ashley; Edwards, Adrian; Lifford, Kate; Abbel, Denise; Cannegieter, Suzanne; Goedegebuur, Jamilla; Kempers, Eva; Gulbech Ording, Anne; Kruip, Marieke; Portielje, Johanneke; Søgaard, Mette; et al. (International Journal of Population Data Science, 2024)
Background and Objectives For patients receiving end-of-life care, adjusting polypharmacy and deprescription of potentially harmful medicines are important impactors on quality-of-life. Antithrombotic therapies (ATT) are used by 30-50% of patients with cancer, rising to 80% in older cancer patients, and are often continued until a quality-of-life-impacting bleeding event, or a patient is physically unable to take oral medication. We aimed to describe the use of ATT and occurrence of clinical outcomes in patients with cancer during end-of-life care. Approach Linked health and administrative data in SAIL were used to identify end-of-life cancer patients diagnosed in Wales, focusing on cancer types with an estimated 1-year survival time. Survival analysis was used to describe current ATT usage and to investigate the associations between ATT usage and major cardiovascular and bleeding events. Results 21,880 individuals were diagnosed with the pre-defined cancer types between January 2013 and December 2019, 5,660 (26%) of these were taking ATT at diagnosis. During the study period 1670 (30%) were discontinued. Median survival time of patients taking ATT at diagnosis was 169 (IQR 158-180) days, while median time to deprescription was 206 (IQR 190-224) days. Among ATT-users diagnosis, 460 (8%) and 900 (16%) experienced a major bleed or a cardiovascular event, respectively, within 1 year following diagnosis, compared to 1100 (7%) and 1930 (12%) among those who were not prescribed ATT at diagnosis. Conclusions and Implications Our research highlights the need for careful assessment and management of ATT in the interest of improving quality-of-life for patients with cancer during end-of-life care.